Aktivitas Antibakteri dan Analisis Fitokimia Ekstrak Metanol dari Daun Paku Sarang Burung (Asplenium nidus) - Risky Hadi Wibowo; Redo Setiawan; Welly Darwis; Sipriyadi Sipriyadi; Rochmah Supriati; Alfredi Anis Fadhila Ginting Sinisuka (Jurnal Ilmu Pertanian Indonesia, 2022)
Infectious diseases caused by microbes are increasing; the growth of microbes can be inhibited by using antibiotics. Continuous and inappropriate use of antibiotics causes microbes to become resistant. The resistance can be reduced by finding new sources of antibiotics, one of which is from the bird nest fern (Asplenium nidus). This study aimed to determine the potency and concentration of A. Nidus extract in inhibiting the growth of Staphylococcus aureus ATCC 6538, Escherichia coli ATCC 8739, Pseudomonas aeruginosa ATCC 15442, and Bacillus subtilis ATCC 19659. The extract was prepared using the maceration method with methanol as the solvent. Phytochemical tests include alkaloids, flavonoids, steroids, terpenoids, saponins, phenolics, tannins, and quinones. The minimum inhibitory concentration test was carried out on 12 treatments with three replications; the antimicrobial effectiveness test was carried out on seven treatments with five replications using the disc diffusion method. Phytochemical test results showed A. Nidus contains flavonoids, tannins, saponins, and phenolics. A. nidus extract has the potential to inhibit the growth of the testing pathogenic bacteria, with the most effective concentration on P. aeruginosa of 45% with an inhibitory zone was about 14,16 mm, on E. Coli started of 55% with an inhibitory zone was about 13,68 mm, on B. Subtilis of 65% with an inhibitory zone was about 14,80 mm and S. aureus was 75% with an inhibitory zone of 11,96 mm. Keywords: antibiotics, Asplenium nidus, Infectious disease